2013
DOI: 10.3390/ma6062240
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Compression-Molding of α-Cellulose and Effects of Operating Conditions

Abstract: Commercial α-cellulose was compression-molded to produce 1A dog-bone specimens under various operating conditions without any additive. The resulting agromaterials exhibited a smooth, plastic-like surface, and constituted a suitable target as replacement for plastic materials. Tensile and three-points bending tests were conducted according to ISO standards related to the evaluation of plastic materials. The specimens had strengths comparable to classical petroleum-based thermoplastics. They also exhibited high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…No crystallization temperature has ever been observed for cellulose, but Vaca-Medina et al (Accepted) showed an increase in the crystallinity index of a-cellulose during compression at higher temperatures. Moreover, Pintiaux et al (2013) have tested the mechanical properties of the thermo-compressed samples, and demonstrated an increase in these properties with temperature. Therefore during thermo-compression, crystallization must be associated with another phenomenon responsible for consolidating the powder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No crystallization temperature has ever been observed for cellulose, but Vaca-Medina et al (Accepted) showed an increase in the crystallinity index of a-cellulose during compression at higher temperatures. Moreover, Pintiaux et al (2013) have tested the mechanical properties of the thermo-compressed samples, and demonstrated an increase in these properties with temperature. Therefore during thermo-compression, crystallization must be associated with another phenomenon responsible for consolidating the powder.…”
Section: Discussionmentioning
confidence: 99%
“…Production of bulk cellulose plastic has been investigated recently using a specific high shear and high-pressure device (Zhang et al 2011), a multi-step non-solvent approach (Nilsson et al 2010), or direct compression on cotton linters (Navard 2012). Our group has studied the influence of the compressing operating conditions on a-cellulose compressed materials (Pintiaux et al 2013), and the effect of temperature on the compression of various celluloses (Vaca-Medina et al Accepted).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, ACCs obtained by compression molding of a-cellulose (i.e. similar to MCC) at very high pressure (>100 MPa) and high temperature (>150 C) exhibit specimens with flexural modulus also around 7 GPa but flexural strength of 43 MPa [39]. These values emphasize the key role of the chemical bonding between the cellulose nanocrystals, and denote effective stress transfer within the material.…”
Section: Mechanical Propertiesmentioning
confidence: 96%
“…However, the solution casting method, the most-commonly used method for pectin film production, has a high demand of energy. In this work heat compression molding technique, with lower energy demand compared to casting [27,28], was employed for production of pectin films. Furthermore, the potential of the fungal biomass for enhancement of the pectin films was investigated.…”
Section: Resultsmentioning
confidence: 99%